The overview of the knowledge level of hypertension prevention and quality of life in Wirobrajan, Yogyakarta - Putra, Anggara Ersa; Sari, Prita Anggraini Kartika; Saputri, Ginanjar Zukhruf (Universitas Ahmad Dahlan, 2023)
Hypertension is a non-communicable disease that is a global problem whose prevalence increases with age. Knowledge is important for a person to evaluate himself. Both hypertension and knowledge can affect a person's quality of life. The purpose of this study was to provide an overview of the level of knowledge about hypertension and the quality of life of the older adults in RW 08 and RW 09 Wirobrajan. The research method used is descriptive-analytic research with inclusion criteria for elderly aged ≥ 60 years. The knowledge test about hypertension and quality of life uses a questionnaire and the EQ-5D3L. The results were 69 older women 67%, education level ≤ 9 years 52%, and history of hypertension 74%. Older adults have a high level of knowledge, with the highest to lowest dimensions being lifestyle (86%), treatment (75%), definition (68%), complications (56%) and adherence to therapy (43%). The EQ5D-3L measurement report showed that the domain scores of no problems with self-care, anxiety/depression, mobility, usual activities, and pain/discomfort were (84.1; 79.7; 73.9; 73.9, and 69.7) %. It was concluded that most of the knowledge and quality of life of the elderly in the Wirobrajan area were in the high category, with the highest domain being self-care and the lowest being pain/discomfort. Further research is needed regarding the relationship between the level of knowledge and the quality of life of older adults. Keywords: Elderly, Hypertension, Knowledge, Quality of life